The Relationship Between Study Habits and Student Learning Outcomes in Mathematics Class V SD 106806 Cinta Rakyat - Daitin Tarigan; Winni Nataly K Purba (PT FORMOSA CENDEKIA GLOBAL, 2023)
The purpose of this study was to determine the relationship between Study Habits and Mathematics Learning Outcomes of Class V students at SDN 106806 Cinta Rakyat. This research includes correlation research with quantitative methods. The sample of this study used the Probability Sampling Technique, namely the VA class of 27 people. Data collection in this study was carried out with instruments. Data analysis techniques use the Product Moment correlation formula and t-test. The results of this study indicate that the study habits of students at SDN 106806 Cinta Rakyat are in the Good category with an average score of 28.25 while for Mathematics learning outcomes students are in the Good category with an average of 86.19. Henceforth, the hypothesis is accepted or Ha which states that there is a significant relationship between study habits and mathematics learning outcomes of fifth grade students at SDN 106806 Cinta Rakyat. This is proven based on the results of the correlation test with the Product Moment technique found rcount > rtable (0.819> 0.381) with a significant level of 0.05. To find out the contribution of the X and Y variables, the formula R2 x 100% = (0.819)2 x 100% = 67.07% is used so that it can be said that the study habits of fifth grade students at SDN 106806 Cinta Rakyat have a 67.07% relationship with learning outcomes. Mathematics Class V SDN 106806 Cinta Rakyat.